Ageing and Health in the Transition Countries of Europe - the Case of Hungary - Etelka Daroćzi (Hungarian Demographic Research Institute, 2007)
Within less than one hundred years during the 20th century, the transition countries of Europe2 – as they are labelled today – experienced two radical social transformations. The communist take-over was the first which reached them at various points of time between 1917 and 1949. The period of communism lasted about 70 years for the first member-republics of the Soviet Union3 and about 40–50 years in other transition countries. The second, more recent, turbulence happened as a surprise, almost the same years, around 1989–1991. The totalitarian regimes collapsed in a split second of human history. Their surviving peoples (re)gained political independence and were staggered to witness a less traumatic though painful exercise: establishing new, democratic institutions and transforming the command economies into market economies. From a global perspective it is certainly justified to identify these countries as a distinct group. They formed a consolidated ideological, political, economic and (partly) military system, isolated from the free capitalist Europe by the iron curtain4. But beyond the curtain, despite all efforts for homogenisation, the extremely diverse climatic and geographical conditions, deep historical roots, complex cultures, numerous languages, ethnicities, religions, a wide range of local practices in production, distribution, consumption, teaching and heeling etc. have all left their imprints, now openly and widely perceptible, also in demographic
Keywords: 300; Fertilität; Familie; Soziale Werte; Demographischer Übergang; Ungarn